Analysis of Difficulty of PGSD Students in Making Research Instruments - Dyah Indraswati; Deni Sutisna; Mohammad Archi Maulyda; Arif Widodo; Ketut Sri Kusuma Wardani (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
The research aims to identify students difficulties in making research instruments and analyzing the factors of the students difficulties in making research instruments. This type of research is descriptive with a qualitative approach. The study was conducted on 41 students of elementary school teacher Education (PGSD) semester seven year 2019/2020 Faculty of Training and Education science of Mataram University. Data collection techniques using interviews and documentation. Data analysis techniques include data reduction, data presentation, and conclusions. The results showed, the biggest difficulties experienced by students when arranging instrument items and testing and analyzing the validity and reliability of the instruments to be worth using. As much as 40% of research instruments compiled by PGSD students deserve to be used, 40% of instruments still require revision, and 20% of unworthy instruments in meaning need to be proven validity and reliability. The factors that led to students of PGSD Mataram University have difficulty in making research instruments, among others: the lack of interest in reading thus experiencing confusion in distinguishing the conceptual definition and operational definition, the unknowing to ask if there are things that are less understandable, the lack of understanding the substance in each process they do so that there is often a discrepancy between the processes that one with the other, the students are less thorough, and they have their own views on the research.